Enhanced biomass, lipid and bioactive compounds from CRISPR-Cas9, CRISPRi and ASGARD based genetically modified microalgae: a promising frontier in biotechnology - Josephine, A.; Kumar, T.S.; Ashok Kumar, S.; Dharani, G.; Kirubagaran, R. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2025)
In recent years, genetic engineering has witnessed a remarkable shift towards harnessing the potential of microalgae for various applications including enhanced biomass production, biofuel production, wastewater treatment and the synthesis of valuable bioactive compounds. Our previous study has proven that genetic modifications of Chlorella vulgaris Beijer. using random mutagenesis significantly enhanced the lipid content, making it more ideal for biofuel production in C. vulgaris. However, efficient genetic engineering tools are still lacking in their ability to simultaneously augment the overall production of biomass and bioactive compounds. The present review discusses the most recent tools and strategies that are used to engineer microalgal strains, from culturing to modern gene-editing techniques like Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and CRISPR associated protein 9 (CRISPR-Cas9). Numerous studies have reported that targeted nucleases represent a remarkable advancement in genome manipulation, offering unparalleled precision. A novel variant of CRISPR, known as CRISPRi technique was reported to yield significant outcomes in microalgal species even under non-stressful conditions. Further, to curtail the bottlenecks due to high guanine-cytosine contents of DNA in microalgae, a new approach such as Adaptive Single Guide Assisted Regulation DNA (ASGARD) was explored along with CRISPRi, which yielded higher lipid and protein contents, thus finding indispensable applications in industry. Hence, this review effectively conveys the advantages and disadvantages associated with various genetic engineering tools and the complexity and precision required in genetic modification and the resulting potential for improved biomass, lipid and bioactive compounds productivity in marine microalgal species.